Energy harvesting from pavements and roadways: A comprehensive review of technologies, materials, and challenges. (3rd February 2019) - Ahmad, Saifuddin; Abdul Mujeebu, Muhammad; Farooqi, Mohd. Ahmadullah
Summary: Energy harvesting from pavements has been a topic of extensive research in the recent past. This domain has attracted not only the research community but also the industry and governmental authorities. The various sources exploited for energy harvesting from pavements and roadways are solar radiation, mechanical energy dissipated due to moving vehicles and pedestrians, geothermal energy, rainwater, and wind. This article presents an exhaustive and updated review of all potential means of energy harvesting from these sources. Following the introductory section, the article sequentially covers the energy harvesting methods and their research progress, materials, development of practical systems, commercial status, comparison of technologies, challenges, and concluding remarks. This study reveals that there is wide scope for further research and feasibility studies, which could lead to a wide‐spread implementation of the various technologies for energy harvesting from pavements and roads.